Numerical investigation of groundwater flow systems and their evolution due to climate change in the arid Golmud river watershed on the Tibetan Plateau - Xiao, Yong; Liu, Kui; Zhang, Yuqing; Yang, Hongjie; Wang, Shengbin; Qi, Zexue; Hao, Qichen; Wang, Liwei; Luo, Yinfei; Yin, Shiyang (Frontiers in Earth Science, 2022)
Climate warming is the greatest future challenge to the hydrosphere and the human community, especially in arid and semiarid regions. This study took the Golmud river watershed on the Tibetan Plateau as an example to numerically identify the development of groundwater flow systems in a large arid sedimentary basin and explore what would the dramatic climate warming pose on groundwater flow system. The numerical results show that the Golmud river watershed has developed three hierarchical groundwater flow systems. River seepage is the predominant recharge for the groundwater systems inside the basin. The local groundwater flow system discharges some 82.69% of all groundwater in the basin, followed by the intermediate system with 14.26% and the regional system with 3.05%. The local system is mainly distributed in the shallow area of the alluvial-pluvial fan at the piedmont and provides the dominant water resource for human exploitation and oasis ecological usages. Climate warming would increase about 30.78% of the quantity of the recharge water to the groundwater system inside the basin via river seepage due to the increasing precipitation and increased glacier melt in the headwater region of the watershed. These waters would pose disturbances to all groundwater flow systems but to different degrees. The local flow system exhibits the largest response to the climate warming with more than 90% of increased water cycled in and discharged through it. The significant groundwater level rising leads to the trailing edge of the overflow belt at the piedmont moving ∼5 km towards to the mountain pass, which would potentially pose a water disaster to the local region. The influences of climate warming on the intermediate and regional flow system are relatively limited. This study provides a preliminary understanding of the influences of climate warming on the groundwater flow systems in arid endorheic basins and is essential for tackling future climate change challenges faced by arid and semiarid regions.